2011
DOI: 10.1007/s10059-011-2277-7
|View full text |Cite
|
Sign up to set email alerts
|

Development of Novel Monoclonal Antibodies that Define Differentiation Stages of Human Stromal (Mesenchymal) Stem Cells

Abstract: Human mesenchymal stem cells (hMSC) are currently being introduced for cell therapy, yet, antibodies specific for native and differentiated MSCs are required for their identification prior to clinical use. Herein, high quality antibodies against MSC surface proteins were developed by immunizing mice with hMSC, and by using a panel of subsequent screening methods. Flow cytometry analysis revealed that 83.5, 1.1, and 8.5% of primary cultures of hMSC were double positive for STRO-1 and either of DJ 3, 9, and 18, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…These observations impair its clinical use by increasing the likelihood of variation to the extent of bone healing. More recently, collagen IV was shown to select for cultured, but undifferentiated MSCs [55]. In contrast, we show that continuous supplementation with HS-2 similarly upregulates hMSC self-renewal and greatly improves their homogeneity, suggesting that HS-2 would benefit future therapies utilizing cultured hMSCs.…”
Section: Discussionmentioning
confidence: 43%
“…These observations impair its clinical use by increasing the likelihood of variation to the extent of bone healing. More recently, collagen IV was shown to select for cultured, but undifferentiated MSCs [55]. In contrast, we show that continuous supplementation with HS-2 similarly upregulates hMSC self-renewal and greatly improves their homogeneity, suggesting that HS-2 would benefit future therapies utilizing cultured hMSCs.…”
Section: Discussionmentioning
confidence: 43%
“…In undifferentiated cells, type VI collagen was localized exclusively to the cytoplasm. In contrast, when the media were changed to stimulate osteogenesis or adipogenesis, type VI collagen was found localized to the cell membrane and pericellular matrix [50]. More recently, Urciuolo et al (2013) demonstrated that type VI collagen plays a key role in creating the muscle satellite cell niche.…”
Section: Discussionmentioning
confidence: 99%
“…For direct ELISAs, purified mouse DLK1 (0.5-1.0 µg/mL) was coated onto 96-well Maxisorp flat bottom microtiter plates. For cyto-ELISAs, 3T3-L1 and C2C12 cells were cultured in 96-well plates and fixed with 4% NBF at sub-confluence, as previously described [22]. Hybridoma supernatants were then transferred to the wells and plates incubated overnight.…”
Section: Screening Of Hybridoma Supernatantsmentioning
confidence: 99%